A refiner's fire [large type] - Leon, Donna (Leon, Donna. Commissario Guido Brunetti mystery, 2024)
"On an early spring morning, two teenage gangs are arrested after clashing violently in one of Venice's squares. Commissario Claudia Griffoni walks the last of the boys home because his father, Dario Monforte, failed to pick him up. Guido Brunetti is asked to vet Monforte for a job, triggering Brunetti's memory that twenty years earlier Monforts had been celebrated as the hero of a devastating bombing. Yet Monforte had never been awarded a medal. Brunetti discovers the hypocrisy surrounding Monforte's past, culminating in a fiery meeting of two gangs and a final opportunity for redemption"--